Thermally induced microstructural changes in fly ash geopolymers: Experimental results and proposed model - Rickard, William; Kealley, Cat; Van Riessen, Arie (Blackwell Publishing Inc., 2015)
This study presents a proposed model for thermally induced microstructural changes in fly ash geopolymers. Two paste mixes with different as-cured microstructures are evaluated for thermal resistance. One mix was a highly reacted, high-strength geopolymer with a compact microstructure and the other mix had higher degree of unreacted fly ash resulting in a low strength, low-density geopolymer. Changes in the microstructure and bulk properties for each formulation were assessed at 100C temperature intervals up to 1000C using SEM, Q-XRD and physical testing. It was observed that the higher density and apparent lower permeability of the high-strength geopolymer led to it being more vulnerable to dehydration damage. Dimensional and phase changes also caused further strength losses before sintering at higher temperatures promoted strength gains. The low-strength geopolymer was not damaged by dehydration and was better able to accommodate volumetric changes; hence it exhibited an increase in strength after thermal exposure due to the sintering. From these results and others in the literature, a model has been proposed for thermally induced changes in fly ash geopolymers.